Generalization of Semiprime Subsemimodules - Farzalipour, F; Ghiasvand, P (Journal of Bangladesh Academy of Sciences, 2016)
The authors introduce the concept of almost semiprime subsemimodules of semimodules over a commutative semiring R. They investigated some basic properties of almost semiprime and weakly semiprime subsemimodules and gave some characterizations of them, especially, for (fnitely generated faithful) multiplication semimodules. They also study the relations among the semiprime, weakly semiprime and almost semiprime subsemimodules of semimodules over semirings. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 187-197, 2016